DOCUMENTATION BARRIERS FOR REFUGEES DURING THE COVID-19 PANDEMIC IN INDONESIA: A STUDY IN THE CITY OF LHOKSEUMAWE - Fajri, Muhammad; Aiyub Kadir, M. Yakub (Student Journal of International Law, 2022)
This paper assess the documentation barriers for handling refugees during Covid-19, including vaccination with reference to refugees in City of Lhokseumawe, Aceh Province, Indonesia. Equally, the roles of UNHCR, the government, and the health office also be taken into account. The results showed that the role of UNHCR, the government, and the health service in handling refugees has not optimally run because the shelter provided was not adequate, while conducting PCR tests, distributing masks and hand sanitizer, and even vaccinating refugees is limited. The national rules related to the vaccination of Rohingya refugees are contained in Article 27 of the 2016 Presidential Regulation on Handling Refugees from Abroad. However, there are barriers and challenges for vaccinating refugees such as the documentation barriers and the shotage of logistics. There are suggestions to add adequate shelters, provide masks and hand sanitizer, and carry out PCR tests in every activity carried out by refugees under the public health principle. So it should be there is no documentation barriers when public health is demonstrating